Pola Dakwah Kyai dalam Membangun Sosio-Religius Masyarakat di Kecamatan Leces Kabupaten Probolinggo - Muhammad Nabat Ardli (Risâlah Jurnal Pendidikan dan Studi Islam, 2024)
In Islam da'wah activities are the main of the development of Islam, which has always been in the spotlight of scholars to improve the morals of mankind. Da'wah in Indonesia can't be separated from the figure of Kyai who is capable of internalizing the values of Islamic teachings in the people's lives. Every kyai has his own way of da'wah pattern in his da'wah approach according to the socio-cultural conditions of his mad'u as carried out by the three kyai in Leces District, Probolinggo Regency, they are: Kyai Hasan, Kyai Abbas and Kyai Barizi. This study aims to reveal the pattern of kyai's da'wah in building socio-religious society in Leces District, Probolinggo Regency. with sub-focuses including: (1) the role of da'wah, (2) da'wah patterns of kyai. This research uses qualitative research that uses a descriptive analysis approach in field studies. Data collection has taken by observation, in-depth interviews, and documentation studies. Data analysis techniques include data reduction, data presentation and conclusion. The results showed that: (1) Kyai in Leces has the same da'wah role in society. Such as leading congregational prayers, wiridan, recitation of the Qur'an and also prayer, but there are also kyai who are trusted as protectors, activators, and problem solvers who can solve community problems. (2) The pattern of kyai da'wah in Leces Subdistrict has different strategies and approaches based on the socio-cultural conditions of the community and also the scientific basis and experience of each kyai, such as the approach of recitation, education, tarekat and politics.